Therapeutic management of cutaneous and genital warts - Ockenfels, Hans Michael (Journal der Deutschen Dermatologischen Gesellschaft, 2016)
During their lifetime, at least 10 % of the population will be infected by human papillomaviruses (HPV), clinically characterized by the formation of cutaneous or genital warts. Although warts are ubiquitous, there are no defined treatments. Especially in the first six months, warts frequently resolve without therapeutic intervention. This complicates the interpretation of study data, given that many studies do not differentiate between newly infected patients and those with infections that have persisted for a long time. Similarly, most studies do not take location, size, and thickness of lesions into account, either. The objective of the present review article is to analyze the study data currently available, taking into consideration both subtypes and locations - factors exceedingly crucial in clinical practice. In particular, the distinction between new-onset and chronic recalcitrant warts is reflected in a therapeutic algorithm. In the case of genital warts, the algorithm is more clearly determined by the extent of the area affected rather than the longevity of lesions. In immunocompetent individuals, any therapeutic intervention must be aimed at achieving complete resolution.